Futures prices in a production economy with investment constraints - Kogan, Leonid 1974-; Livdan, Dmitry; Yaron, Amir 1964- (National Bureau of Economic Research, 2005)
"We document a new stylized fact regarding the term-structure of futures volatility. We show thatthe relation between the volatility of futures prices and the slope of the term structure of prices isnon-monotone and has a 'V-shape'. This aspect of the data cannot be generated by basic modelsthat emphasize storage while this fact is consistent with models that emphasize investmentconstraints or, more generally, time-varying supply-elasticity. We develop an equilibrium model inwhich futures prices are determined endogenously in a production economy in which investment isboth irreversible and is capacity constrained. Investment constraints affect firms' investmentdecisions, which in turn determine the dynamic properties of their output and consequently implythat the supply-elasticity of the commodity changes over time. Since demand shocks must beabsorbed either by changes in prices, or by changes in supply, time-varying supply-elasticity resultsin time-varying volatility of futures prices. Calibrating this model, we show it is quantitativelyconsistent with the aforementioned 'V-shape'; relation between the volatility of futures prices and the slope of the term-structure"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Futures -- Econometric models